Multiple Robotic Fish’s Target Search and Cooperative Hunting Strategies - Yongyue An; Shuqin Li; Da Lin (Institute of Advanced Engineering and Science, 2014)
Multi-robotic fish’s cooperative hunting is through that the robotic fish groups’ collaboration and against, ultimately achieves the purpose of encirclement target; there is important significance to realize security of the underwater group. This paper studied the problem of multi-robotic fish’s target search and cooperative hunting, discussed on the multi-robotic fish’s group size, conditions of search target and hunting successful, conditions of failure successfully. Proposed the partition global search strategy, hunt-robotic fish use a hunting strategy that based on dynamic surrounding point, and designed intelligent escape strategy for invasion-robotic fish. A simulation experience is conducted to verify the hunting strategy and escape strategy that proposed in this paper, and the results show that on the basic of fast search to the target, multi-robotic fishes can achieve hunting task efficiently, but also reflects the game against behavior between the intruders and hunters. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3907